Polacy w Berlinie – granice i pogranicza - Agnieszka Szczepaniak-Krol (Etnografia Polska, 2012)
This article describes how Polish-German state border influenced the migration of Poles to Germany after World War II, their adaptation in the host society and relations among Polish migrants. For centuries Polish-German relations were shaped by the view of border separating both countries. According to the state policy the western border of Poland was supposed to be closed from the end of the Second World War. Many Poles dreamed about migration to Western Europe, including Germany. Migrants’ adaptation strategies, their integration, identity and mutual perception of Poles and Germans were influenced by the strictly guarded border. This situation started to change only in 1990s. Democratic changes in Poland and Germany at the end of the 20th century allowed people to cross the border freely. This way Polish-German border became a  borderland understood as the space where two cultures meet and overlap. This borderland extends deep into Germany (and Poland as well), including Berlin. The liquidation of physical borders started presumably durable process of changes in the relationship between Poland and Germany. However mentioned changes didn’t eliminate various barriers between different categories of Polish migrants in Germany having their own targets, political strategies, visions of the future, etc.